Investigation of the Influence of a Turnout Cross on Vertical and Horizontal Deformations of a Pneumatic Spring of High-Speed Rolling Stock - Kuzyshyn, A. Ya.; Kovalchuk, V. V.; Kostiv, N. V. (Science and Transport Progress, 2024)
Purpose. The aim of the study is to determine the values of vertical and horizontal deformations of the pneumatic spring of high-speed rolling stock during the movement of the test setup along the cross of the switch in the forward and reverse directions. Methodology. To determine the deformations of the pneumatic spring, a special test bench consisting of a pneumatic spring and specialized measuring equipment was developed. The deformations of the air spring in the vertical and horizontal planes were measured using high-frequency potentiometric linear displacement sensors, the signals from which were read using a programmed analog-to-digital converter. To obtain reliable data on the deformations of the air spring, six passes of the test bench were made in the forward and reverse directions of the cross member. Findings. A methodology for dynamic testing of a pneumatic spring of high-speed rolling stock under conditions of movement along the crosshead of a turnout in the forward and reverse directions was developed. The records of vertical and horizontal deformations of the pneumatic spring of high-speed rolling stock under the conditions of movement along the crossover of a switch were obtained. It is established that the deformations of the pneumatic spring in the vertical plane are higher than those in the horizontal plane. The average value of the vertical deformations of the pneumatic spring in the forward direction is 3.15 mm, which is 9.98 % higher than the average value in the opposite direction of the test unit’s movement along the cross-section of the switch. In the horizontal direction, this difference in deformation of the air spring is 25.1 %. Originality. For the first time, the vertical and horizontal deformations of the pneumatic spring of high-speed rolling stock under the conditions of movement along the crossbar of a switch were determined, taking into account the direction of movement, forward and reverse. Practical value. Determining the values of deformations of the pneumatic spring will allow to study its dynamic characteristics in different operating conditions of rolling stock, and at the design stage to select the appropriate characteristics of the pneumatic spring suspension system and determine the dynamic and safety indicators of rolling stock.